Analysis of water quality, feed efficiency, and growth performance of vannamei shrimp in circular HDPE ponds - Mawaddah, Naflah; Halim, Abdul; Ariwibowo, Dimas Agung (Journal of Marine Resources and Coastal Management, 2025)
Intensive shrimp aquaculture has grown rapidly in recent years, requiring efficient pond management systems to ensure sustainability and productivity. This study aimed to evaluate the cultivation performance of Litopenaeus vannamei (vannamei shrimp) in High-Density Polyethylene (HDPE) round ponds at a shrimp aquaculture facility in Prigi, East Java, Indonesia. Two ponds (BO1 and BO2) were observed through various cultivation phases, including pond and media preparation, feed and water quality management, growth monitoring, harvesting, disease prevention, and waste treatment. The ad libitum and blind feeding methods were used without feeding rate calculations, and water quality parameters were monitored regularly. Results showed that pond BO1 performed well with a survival rate of 72.69%, an FCR of 1.37, and steady growth (ABW and ADG), indicating effective management. In contrast, pond BO2 experienced significant mortality and poor growth due to early stress from excessive water current caused by oversized paddlewheels, resulting in a survival rate of only 6.95% and an FCR of 4.41. Waste management was conducted using a sedimentation-based Wastewater Treatment Plant (WWTP) without the use of chemicals. These findings highlight the critical role of mechanical suitability and integrated management practices in ensuring successful shrimp cultivation in intensive systems.